Humanisme Pendidikan Islam Perspektif Bediuzzaman Said Nursi - ma'ruf, kharis - (Analisis: Jurnal Studi Keislaman, 2017)
Islamic education humanism has an important position to form a complete personal figure. This study will describe the Bediuzzaman Said Nursi’s thought related to Islam and humanism. This research is qualitative research, with the object of research on library materials with a comprehensive approach, interpretation and inductive approach in drawing conclusions. The results of the study show Said Nursi in the practice of Islamic education has the character of religious humanism thinking, which is a religious concept that places humans as human beings in accordance with the purpose of creation by the Creator, as well as the teaching efforts of the sciences with a foundation that remains in the faith, understanding the Koran, and synergy scientific. This concept is an effort to unite religious values with humanity. Thus, the humanism of Islamic education in the perspective of Bediuzzaman Said Nursi, is a concept that is able to develop human potential both worldly and ukhrowi aspects so as to be able to create balanced human beings in relation to fellow beings (hablun minannas) and with the Creator (hablun) minallah).